A reference panel of 64,976 haplotypes for genotype imputation - Kretzschmar, W; Mahajan, A; Sharp, K; McCarthy, M; Haplotype Reference Consortium (Nature Publishing Group, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.